Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 2 - Nonlinear Functions - 2.4 Exponential Functions - 2.4 Exercises: 10



Work Step by Step

The answer is B, because when x=0, $-2+3^{-x} = -2+1 =-1$ So $y=-1$. And also when x=-1, $-2+3^{-x} = -2+ 3 =1$ So $y = 1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.